2002
DOI: 10.1007/s00467-002-0911-5
|View full text |Cite
|
Sign up to set email alerts
|

Nail-patella syndrome. Overview on clinical and molecular findings

Abstract: Nail-patella syndrome (NPS) is a rare autosomal dominant pleiotropic disorder characterized by dysplasia of the nails, patellar aplasia or hypoplasia, iliac horns, dysplasia of the elbows, and frequently glaucoma and progressive nephropathy. The recent identification of the causative gene for this syndrome has initiated further studies of the phenotype and molecular pathogenesis of kidney disease in NPS. The gene underlying NPS, LMX1B, is a LIM-homeodomain transcription factor involved in normal patterning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
133
0
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 54 publications
(124 reference statements)
1
133
0
14
Order By: Relevance
“…Previous ultrastructural studies of renal biopsy specimens of the latter patient demonstrated typical GBM anomalies characteristic for NPS. 33 None of the unaffected relatives of NPS family 26 were reported to have nephropathy.…”
Section: Nephropathymentioning
confidence: 99%
“…Previous ultrastructural studies of renal biopsy specimens of the latter patient demonstrated typical GBM anomalies characteristic for NPS. 33 None of the unaffected relatives of NPS family 26 were reported to have nephropathy.…”
Section: Nephropathymentioning
confidence: 99%
“…Hastalık, tırnaklarda bozukluklar, radius başı hipoplazisi, posteriyor iliyak çıkıntılar üstünde veya kenarında 'iliyak boynuz''ların gelişmesi, patellanın hipoplazisi veya tamamen yokluğu ile karakterizedir. [17] Patellanın radyografik olarak tespit edilebilen bozuklukları, oval veya üçgen şekilli patella veya patella baja'dır. Bu tarz patellar bozukluklar sık görülmesine rağmen, tırnak-patella sendromunda belirgin fonksiyonel yetmezlik nadiren tespit edilir.…”
Section: Ekstansör Mekanizma Duplikasyonuunclassified
“…[18,19] Ek olarak, lateral femoral kondil hipoplazisi, interkondiler çentikte genişleme, lateral femoral kondilde osteokondral defekt, tibial tüberkülde belirginleşme, fibula başı hipoplazisi, genu valgum veya varum, pes ekinovarus, kalça displazisi ve büyük eklem kontraktürleri görülebilir. [17,20] Nadiren, aşırı genu valgum gelişen olgularda, düzeltici tibial osteotomilere gereksinim duyulabilir.…”
Section: Ekstansör Mekanizma Duplikasyonuunclassified
“…1,2 The LMX1B gene is responsible for the NPS and for NPS associated with OAG, and it encodes a LIM-homeodomain protein. 1 A wide inter-and intrafamilial variability has been described for skeletal abnormalities, presence and severity of nephropathy and ocular anomalies. No significant genotype -phenotype correlation has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…No significant genotype -phenotype correlation has been reported. 1 The LMX1B gene plays a pivotal role in embryo development in particular for limb development, kidney morphogenesis and development of the anterior segment of the eye. 3 -5 Phenotype variability might well be ascribed to interactions with other developmental genes, especially considering the properties of the LMX1B gene, whose LIM domain favors protein -protein interaction.…”
Section: Introductionmentioning
confidence: 99%